Pelatihan Robotika Tempat Sampah Pintar dan Miniatur Selektor Otomatis untuk Guru Elektronika SMP BPK PENABUR - Kevin Sutanto; Marvin Yonathan Hadiyanto; Johansah Liman; Eddy Wijanto; Ivan Tanra; Indra Karnadi; Richie Estrada; Budi Harsono (Jurnal Atma Inovasia, 2026)
The advancement of robotics technology enables project based instructional media to be integrated into secondary education as a means to enhance technological literacy and problem solving skills among students. This community engagement program aimed to enhance the competencies of electronics subject teachers at SMP BPK PENABUR Jakarta through training on the design and implementation of basic Arduino based robotic systems. The training was conducted onsite using a hands-on approach and featured two applied projects: an ultrasonic based smart trash bin and a conveyor based automatic object selector. Participants gained practical experience in sensor introduction, simple block programming, and system functionality testing. Evaluation results indicated that the training was positively received and considered relevant to the school’s instructional needs in integrating technology into learning modules. This program contributed to improving teachers readiness to implement applied robotics learning and to strengthening STEM literacy foundations at the secondary education level.